2014
DOI: 10.1016/j.celrep.2014.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis-Driven Systemic Immune Response Alters SAM Metabolism through the FOXO-GNMT Axis

Abstract: Sterile inflammation triggered by endogenous factors is thought to contribute to the pathogenesis of acute and chronic inflammatory diseases. Here, we demonstrate that apoptosis-deficient mutants spontaneously develop a necrosis-driven systemic immune response in Drosophila and provide an in vivo model for studying the organismal response to sterile inflammation. Metabolomic analysis of hemolymph from apoptosis-deficient mutants revealed increased sarcosine and reduced S-adenosyl-methionine (SAM) levels due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 66 publications
2
102
1
Order By: Relevance
“…In agreement, innate immune responses to tissue damages ( a.k.a . sterile inflammation) were shown to activate FOXO in an invertebrate model (Obata et al., 2014). It is plausible that axonal degeneration due to loss of proteostasis or FOXO function during aging initiates reactive gliosis to prevent further neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, innate immune responses to tissue damages ( a.k.a . sterile inflammation) were shown to activate FOXO in an invertebrate model (Obata et al., 2014). It is plausible that axonal degeneration due to loss of proteostasis or FOXO function during aging initiates reactive gliosis to prevent further neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the wing pouch (WP) region of wing discs might be a suitable model to study regenerative growth (13,24). WP-Gal4 is expressed predominantly in the wing pouch region and haltere discs from the early stage of larvae (21) (Fig. S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of metabolites was performed using ultra-high-performance liquid chromatography equipped with tandem MS, TQD (UPLC-MS/MS; Waters) based on a previous study (21,36). Immunostaining, fly culture, and other experimental procedures have been performed following protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations